An Analysis of Student Responses in Online Learning-Based Comic Video Module Creative Realistic Mathematics on Integer Operation Material - Tetty Natalia Sipayung; Imelda Imelda; Tatag Yuli Eko Siswono; Masriyah Masriyah (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
Everyone’s perspective is different. Likewise, the student’s perspective on mathematics. It is undeniable that most childran claim that mathematics is difficult. Behind the statement, of course, there is a reason for the child. This is related to student responses when studying in mathematics class. One alternative to knowing student responses can be found by conducting research. Therefore, qualitative research is needed to analyze student responses. The application of learning using creatibe module comics based on a realistic mathematics approach has been implemented for all students of class VII-B at SMP Santo Yoseph Medan in the 2020/2021 Academic Year. In this study students’ responses to the application of learning were analyzed specifically for integer operation material. The learning is carried out online based on the creative realistic mathematics video comic module in the Google Classroom. The instrument used was a student response questionare which was presented via google form. Based on the results of data collection that has been done, it is concluded that the student’s responses are positive to learning using the creative module comic based on realistice mathematics approach. It is based on obtaining a high score on the average percentage of interest and benefits that students derive from implementation.